Colour–Grapheme Synesthesia Affects Binocular Vision - Paffen, Chris L.; Van der Smagt, Maarten J.; Nijboer, Tanja C. (Frontiers in Psychology, 2011)
In colour-grapheme synaesthesia, non-coloured graphemes are perceived as being inherently coloured. In recent years, it has become evident that synaesthesia-inducing graphemes can affect visual processing in a manner comparable to real, physical colours. Here, we exploit the phenomenon of binocular rivalry in which incompatible images presented dichoptically compete for conscious expression. Importantly, the competition only arises if the two images are sufficiently different; if the difference between the images is small, the images will fuse into a single mixed percept. We show that achromatic graphemes that induce synaesthetic colour percepts evoke binocular rivalry, while without the synaesthetic percept, they do not. That is, compared to achromatically perceived graphemes, synaesthesia-inducing graphemes increase the predominance of binocular rivalry over binocular fusion. This finding shows that the synaesthetic colour experience can provide the conditions for evoking binocular rivalry, much like stimulus features that induce rivalry in normal vision.